Remote Real-time Status Monitoring System for Shenhua Locomotive Based on WebGIS - Junfeng ZHANG; Fei LI (机车电传动)
For monitoring Shenhua locomotive status in real time, such as location, speed, etc., to dispose on-board failure of locomotive, and improving operation efficiency and safety, remote real-time status monitoring system for Shenhua locomotive based on WebGIS was designed with functions such as locomotive location, track trailing, status monitoring, failure alarm, emergent dispose, etc. The practical application for this system showed that, illustratig locomotive real-time status and failure data by WebGIS could efficiently help ground operation & maintenance staffs to monitor locomotive status in time and improve efficiency and accuracy of locomotive failure analysis and dispose.